2022
DOI: 10.3389/fphar.2022.820071
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine: An Active Ingredient of Chinese Herbal Medicine With Therapeutic Potential in Acute Kidney Injury and Renal Fibrosis

Abstract: As an increasing public health concern worldwide, acute kidney injury (AKI) is characterized by rapid deterioration of kidney function. Although continuous renal replacement therapy (CRRT) could be used to treat severe AKI, effective drug treatment methods for AKI are largely lacking. Tetramethylpyrazine (TMP) is an active ingredient of Chinese herb Ligusticum wallichii (Chuan Xiong) with antioxidant and anti-inflammatory functions. In recent years, more and more clinical and experimental studies suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 122 publications
1
13
0
Order By: Relevance
“…Pharmacological studies have found that TMP inhibits platelet aggregation, reduces blood viscosity, scavenges free radicals, protects cardiovascular and cerebrovascular vessels, and dilates renal blood vessels ( Zhao et al, 2016 ). Given its antioxidant, anti-inflammatory, and anti-apoptotic effects, many studies have focused on the benefits of TMP in AKI ( Li and Gong, 2022 ). Cisplatin causes an increase in MDA, Nitric Oxide (NO), and inducible nitric oxide synthase (iNOS) levels and a decrease in GSH, GST, and SOD levels, which can be restored to near-normal levels by TMP intervention, suggesting that TMP inhibits oxidative stress, thus, has a dose-dependent protective effect against cisplatin-induced tubular toxicity ( Ali et al, 2008 ; Liu et al, 2008 ).…”
Section: Botanical Drug Metabolites With Research Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies have found that TMP inhibits platelet aggregation, reduces blood viscosity, scavenges free radicals, protects cardiovascular and cerebrovascular vessels, and dilates renal blood vessels ( Zhao et al, 2016 ). Given its antioxidant, anti-inflammatory, and anti-apoptotic effects, many studies have focused on the benefits of TMP in AKI ( Li and Gong, 2022 ). Cisplatin causes an increase in MDA, Nitric Oxide (NO), and inducible nitric oxide synthase (iNOS) levels and a decrease in GSH, GST, and SOD levels, which can be restored to near-normal levels by TMP intervention, suggesting that TMP inhibits oxidative stress, thus, has a dose-dependent protective effect against cisplatin-induced tubular toxicity ( Ali et al, 2008 ; Liu et al, 2008 ).…”
Section: Botanical Drug Metabolites With Research Potentialmentioning
confidence: 99%
“…At present, Chinese medicine has received strong support from the World Health Organization and is included in Chapter 26 of the 11th edition of the Global Medical Program. The renoprotective effects of some Chinese medicinal formulas and metabolites have received widespread attention and have been studied in multiple AKI models, including DI-AKI ( Wang et al, 2019 ; Li and Gong, 2022 ; Rui et al, 2022 ; Zou et al, 2022 ). In this review, whether Chinese meteria medica and their preparations or monomers can improve DI-AKI and their potential mechanisms of action were explored.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of AKI-CKD transition is a complex process involving inflammatory damage, G2/M cell cycle arrest, and oxidative stress (OS), and these processes ultimately lead to or aggravate renal fibrosis. 4,5 Understanding the precise underlying molecular mechanisms of AKI-CKD transition is imperative for identifying early intervention options to improves patient prognosis. [6][7][8] Cellular senescence is involved in the pathomechanisms of different forms of kidney damage including AKI and CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Renal maladaptive repair after AKI results in the development of renal interstitial fibrosis, supporting the existence of AKI‐CKD transition. The progression of AKI‐CKD transition is a complex process involving inflammatory damage, G2/M cell cycle arrest, and oxidative stress (OS), and these processes ultimately lead to or aggravate renal fibrosis 4,5 . Understanding the precise underlying molecular mechanisms of AKI‐CKD transition is imperative for identifying early intervention options to improves patient prognosis 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Tetramethylpyrazine (ligustrazine, TMP) is an alkaloid monomer extracted from the dried rhizome of the Chinese herbal medicine Ligusticum striatum DC . (Chuan Xiong) [ Figure 1 ( Li and Tetramethylpyrazine, 2022 )]. Chuan Xiong is a vital ingredient in Buyanghuanwu decoction, Houshiheisan, and Naoxintong capsules.…”
Section: Introductionmentioning
confidence: 99%